Multivalent Interactions between an Aromatic Helical Foldamer and a DNA G‐Quadruplex in the Solid State. (19th August 2016) - Mandal, Pradeep K.; Baptiste, Benoît; Langlois d'Estaintot, Béatrice; Kauffmann, Brice; Huc, Ivan
Abstract: Quinoline‐based oligoamide foldamers have been identified as a potent class of ligands for G‐quadruplex DNA. Their helical structure is thought to target G‐quadruplex loops or grooves and not G‐tetrads. We report a co‐crystal structure of the antiparallel hairpin dimeric DNA G‐quadruplex (G4 T4 G4 )2 with tetramer1 —a helically folded oligo‐quinolinecarboxamide bearing cationic side chains—that is consistent with this hypothesis. Multivalent foldamer–DNA interactions that modify the packing of (G4 T4 G4 )2 in the solid state are observed. Abstract : Ligands for G‐quadruplexes : A cationic aromatic helical foldamer and a G‐quadruplex DNA formed a crystallographically resolvable solid‐state assembly stabilized by multivalent interactions. The structure validates the absence of contacts between foldamers and G‐tetrads.